Business Strategy for the Development and Marketing of an HTML 5-based Learning Application for Children with Dyslexia - Aulia, Meidy; Barus, Apriwati (International Journal of Economics and Management, 2023)
Dyslexia is a reading and spelling disorder that affects children's learning ability. Technology-based learning applications have great potential to help dyslexic children overcome learning challenges. The development of HTML5-based learning apps for children with dyslexia has great potential to improve the quality of their learning. However, the success of this app depends not only on the technological aspects, but also on a well-thought-out business strategy. App development should consider the needs and preferences of the end-users, namely children with dyslexia. Features that support differentiated learning and interactive introduction of material are very important. the marketing strategy should focus on the right market segment and craft relevant messages. Effective communication to parents and educators about the benefits of the app is also an important factor. A sustainable business model must be formulated. Options such as subscriptions, direct sales, or a combination of both should be analyzed taking into account long-term financial aspects. Competition analysis and uniqueness of product value should be clear. The app should be able to compete with similar products and offer added value that sets it apart. This research shows that the development and marketing of an HTML5-based learning app for children with dyslexia requires a well-thought-out business strategy. The success of the app depends not only on the quality of the technology but also on how it is positioned in the market and received by the end user. By combining technology, education, and business elements, this app has the potential to make a positive impact in assisting dyslexic children in the learning process.